2008
DOI: 10.1016/j.tox.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and carcinogenicity of methyl isobutyl ketone in F344N rats and B6C3F1 mice following 2-year inhalation exposure

Abstract: Methyl isobutyl ketone (MIBK) is primarily used as a denaturant for rubbing alcohol, as a solvent and in the manufacture of methyl amyl alcohol. Inhalation of vapors is the most likely route of exposure in the work place. In order to evaluate the potential of MIBK to induce toxic and carcinogenic effects following chronic exposure, groups of 50 male and 50 female F344/N rats and B6C3F1 mice were exposed to MIBK at concentrations of 0, 450, 900, or 1800ppm by inhalation, 6h/day, 5 days per week for 2 years. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The mechanism for this was found to be due to the induction of the CYP450 system [ 41 , 42 , 43 ]. Chronic inhalation of an isomer of 2-hexanone (methyl isobutyl ketone, MIBK) was found to cause hepatocellular adenomas and HCC in mice [ 44 , 45 , 46 ]. This was shown to be in part due to the activation of the pregnane X and constitutive androstane nuclear receptors; these receptors are responsible for the regulation of CYP450 activity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this was found to be due to the induction of the CYP450 system [ 41 , 42 , 43 ]. Chronic inhalation of an isomer of 2-hexanone (methyl isobutyl ketone, MIBK) was found to cause hepatocellular adenomas and HCC in mice [ 44 , 45 , 46 ]. This was shown to be in part due to the activation of the pregnane X and constitutive androstane nuclear receptors; these receptors are responsible for the regulation of CYP450 activity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenicity : Currently, no studies assessed carcinogenicity of MIBK following oral exposure. Some evidence of carcinogenic activity were observed in inhalation studies, which reported increased incidences of renal tubule neoplasms in rats and hepatocellular neoplasms in mice at the highest tested dose of 1800 ppm (equivalent to 1725 mg/kg/day for rats and 3171 mg/kg/day for mice) [ 115 , 842 , 844 , 845 , 846 ].…”
Section: Epigenetic Carcinogens or Carcinogens With Uncertain Mode Of...mentioning
confidence: 99%
“…This will result in further costs to ensure the health and safety of personnel and the working environment, as well as the additional cost of installing a flare system in the plant. MIBK is a low boiling point, flammable organic solvent with high toxicity to humans through inhalation, 101 although it does not represent an issue in WWT since it is highly biodegradable. Control measures must be in place to minimise the emission of this solvent to the atmosphere.…”
Section: Solvent Safety Considerationsmentioning
confidence: 99%